Gas sorption and binding site studies in metal organic frameworks - Eyley, J.E. (2017)
This thesis describes the design and synthesis of a series of Cu(II)-paddlewheel based metal organic frameworks (MOFs) for the adsorption of gaseous fuels and pollutants. The frameworks comprise V-shaped pyridyl carboxylate ligands, which are progressively modified to increase gas adsorption capacity and selectivity of the resultant materials. Chapter 1 introduces the history and structure of MOFs, including an exploration of their varied applications. Particular attention is paid to gas adsorption within these materials, considering the best performing materials for each gas discussed. Chapter 2 explores the ability of uncoordinated pyridyl groups to form strong interactions with adsorbed CO2. A new self-interpenetrated Cu(II) MOF (MFM-170) is synthesised from a V-shaped pyridyl carboxylate ligand, in which the pyridyl nitrogen coordinates to the axial site of the interpenetrating net. The porosity and gas adsorption properties of this material are discussed in detail. Chapter 3 describes how functional groups can introduce binding sites into MOFs, strengthening framework-adsorbate interactions and improving gas adsorption capacities. Three isostructural analogues of MFM-170 are synthesised (MFM-171, MFM-172, MFM-173), each with a different functional group directed into the pore. Differences in the gas adsorption properties of these materials are rationalised by identification of CO2 binding sites by IR microspectroscopy and Single Crystal X-ray Diffraction experiments. Chapter 4 draws on knowledge of CO2 binding sites identified in Chapter 3 to selectively target areas of the framework where strongly coordinating functional groups would have the greatest effect of CO2 adsorption and selectivity. A new Cu(II) framework (MFM-175) is reported, incorporating triazole groups directed into the void. The structure, stability and gas adsorption properties of MFM-175 are studied in detail and compared to MFM-170. Chapter 5 investigates the synthesis of a non-interpenetrated analogue of MFM-170 with the aim of liberating the pyridyl nitrogen group to improve framework-adsorbate interactions. A new Cu(II) MOF (MFM-176) is synthesised, featuring a two-fold interpenetrated structure. Nevertheless MFM-176 demonstrates improved selectivity parameters and additionally a promising strategy for the successful synthesis of a non-interpenetrated framework.